A theoretical computerized study for the electrical conductivity of arterial pulsatile blood flow by an elastic tube model. Issue 12 (December 2016) - Shen, Hua; Zhu, Yong; Qin, Kai-Rong
Highlights: An elastic tube model for the electrical conductivity of arterial pulsatile blood flow is developed. The elastic tube model integrates Ling and Atabek's local flow theory with Maxwell–Fricke theory. The effects of wall motion and blood flow velocity on the blood conductivity are investigated by the elastic tube model. The results show that the wall motion is the primary factor to affect the conductivity of flowing blood in arteries. Abstract: The electrical conductivity of pulsatile blood flow in arteries is an important factor for the application of the electrical impedance measurement system in clinical settings. The electrical conductivity of pulsatile blood flow depends not only on blood-flow-induced red blood cell (RBC) orientation and deformation but also on artery wall motion. Numerous studies have investigated the conductivity of pulsatile blood based on a rigid tube model, in which the effects of wall motion on blood conductivity are not considered. In this study, integrating Ling and Atabek's local flow theory and Maxwell–Fricke theory, we develop an elastic tube model to explore the effects of wall motion as well as blood flow velocity on blood conductivity. The simulation results suggest that wall motion, rather than blood flow velocity, is the primary factor that affects the conductivity of flowing blood in arteries.